PENGARUH LATAR BELAKANG PENDIDIKAN, PENGALAMAN KERJA, DAN ETOS KERJA TERHADAP KINERJA PEGAWAI SMA NEGERI 2 PARE KABUPATEN KEDIRI - Dewanti, Melina Astri; Wihara, Dhiyan Septa; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2023)
The background of this research is an institution of State Senior High School 2 Pare, Kediri Regency, on average with graduates from Teacher Education and employees it must be required to have at least a State High School/Equivalent to Bachelor Degree with the major required by the agency. The success and success of school staff at the 2 Pare State Senior High School, Kediri Regency, is an appreciation for employees and not far away from the favorite schools in Pare and its surroundings. Apart from that, the school has a good performance of staff and teaching staff. In this approach available is quantitative. This is used because the data obtained is in the form of numbers. The quantitative method is research that is guided by the philosophy of positivism to examine a certain population or sample and take a random sample by collecting data using statistical data analysis tools. Further research, it is necessary to conduct further research on factors other than educational background, work experience, and work ethic because these three factors in carrying out the employee performance variable get a result of 87% so there is still 13% of employee performance in senior high schools 2 Pare This is because in this study there are still variables or other aspects that can affect employee performance. And I suggest choosing the factors of work loyalty and work motivation.